The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1017/s0031182097001881
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genomic markers confirm the presence of the camel strain (G6 genotype) of Echinococcus granulosus in north-western China

Abstract: Twenty-eight isolates of E. granulosus, collected from humans at surgery, and a range of intermediate hosts, including sheep, cattle and camels from abattoirs in North and South Xinjiang Uygur Autonomous Region, People's Republic of China, were analysed for DNA sequence variation within regions of the mitochondrial cytochrome c oxidase I (COI) and NADH dehydrogenase subunit I (NDI) genes. The isolates were categorized into 2 distinct and uniform genotypic groupings, based on the sequences obtained, and the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 0 publications
4
25
0
Order By: Relevance
“…The presence of E. granulosus genotypes G2, G5, G6 and G9 in humans was confirmed in Argentina and Poland (Guarnera et al, 2004;Rosenzvit et al, 1999;Scott et al, 1997), while in China previous studies from different areas revealed that human infections were caused by the G1 genotype (McManus et al, 1994;Yang et al, 2005;Zhang et al, 1998). However, in Xinjiang Uygur autonomous region the camel strain (G6) was also recently shown to infect humans (Bart et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…The presence of E. granulosus genotypes G2, G5, G6 and G9 in humans was confirmed in Argentina and Poland (Guarnera et al, 2004;Rosenzvit et al, 1999;Scott et al, 1997), while in China previous studies from different areas revealed that human infections were caused by the G1 genotype (McManus et al, 1994;Yang et al, 2005;Zhang et al, 1998). However, in Xinjiang Uygur autonomous region the camel strain (G6) was also recently shown to infect humans (Bart et al, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…The latter genotype was isolated exclusively in samples from the northern area of Xinjiang Uygur (Zhang et al). Zhang et al (1998b), of the Molecular Parasitology Unit at the Australian Center for Tropical Diseases in Brisbane, Australia, studied 16 Echinococcus isolates from Iranian operated patients and from domestic animals in the geographic area of Tehran (including sheep, cattle, goats and camels). The samples were treated using a protocol to analyze the DNA nucleotides and to predict the sequence variations of the amino acids in the mitochondrial cytochrome c oxidase subunit 1 and NADH dehydrogenase genes.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…This disease is practically cosmopolitan and is endemic in Mediterranean regions, Eastern Europe, Central Asia, China, North Africa and South America (Eckert et al, 2000;Jenkins et al, 2005;HELMINTHOLOGIA, 44, 3: 145-149, 2007 Invited Lecture at the 10 th International Helmithological Symposium held in the Hight Tatras, Stará Lesná, Slovak Republic on September 9 -14, 2007 From cestodes to nematodes: 15 years of scientific collaboration between the Parasitological Institute SAS and the Section of Parasitology of the Sapienza University of Rome Romig et al, 2006). Molecular genotyping, using mitochondrial DNA (mtDNA) sequences, has so far identified 10 distinct genetic variants or strains (genotypes G1-G10) within E. granulosus (Bowles & McManus, 1993;Bowles et al, 1994Bowles et al, , 1995Zhang et al, 1998;McManus, 2002;Lavikainen et al, 2003;McManus & Thompson, 2003). They display significant differences in life cycle patterns and host preferences (Thompson & McManus, 2002;McManus, 2002).…”
Section: Echinococcus Granulosusmentioning
confidence: 99%